The Influence Of Occupational Health And Safety (K3) On Employee Performance With Job Satisfaction As An Intervening Variable - Untung Wredhi Lestari; Nurul Qomariah; Ni Nyoman Putu Martini (UNIVED Press, 2025)
The success of human resource management is reflected in the performance of employees who are able to fulfill their responsibilities very well, so that the company can achieve the predetermined targets. The study aimed to determine and analyze the effect of Occupational Safety Health (K3) on employee performance with job satisfaction as an intervening variable study at PT Rolas Nusantara Medika Jember Regency. This research uses quantitative methods. The population studied in this study were employees of PT Rolas Nusantara Medika at 2 Hospitals, 5 Clinics and Head Office offices in Jember Regency, totaling 260 people and sampling using purposive sampling method. The analysis technique used SEM-PLS analysis with the help of Warp-PLS software. The results showed that Occupational Health and Safety (K3) had a positive and significant effect on job satisfaction and employee performance. Job satisfaction has a positive and significant effect on employee performance. Occupational Health and Safety (OHS) and organizational culture have a positive and significant effect on employee performance through job satisfaction.